E1.2 When a child dies. simulating the death of an infant: key practical and communication skills. (4th October 2017) - Akers, E; Cooke, R; Judge-Kronis, L; Brookes, D Moore
Abstract : Background: We piloted a simulation course to address learning needs in both technical and non-technical skills of end-of-life care. Feedback from bereaved parents indicates a knowledge deficit around communication. Scoping professional's views confirmed this, also anxiety about rarely used practical skills. Using simulation to recreate this 'day' is novel and addresses a recognised learning need. 1 Strategy: Simulated scenario: care had been withdrawn on the baby after unsuccessful cardiac surgery with mother (actor) present. The baby was baptised in the HDU, died and was transferred to the mortuary. All steps took place in real time. The learning outcomes were; practical care when immediately before and after death; supporting and communicating with parents; legal aspects of certification and communication with multiple teams about the death; spiritual needs and professional's self-awareness. Results: Candidates fed back following a Quaker-style debrief using words such as enlightening, powerful and honest. A formal evaluation followed; feedback indicated an improved sense of preparedness, lessened anxiety and empowerment. Follow up will be undertaken to gauge the impact of this intervention following experience of a child dying. Discussion: In implementing this pilot course, significant learning needs have been met for a small number of candidates, particularly the experience of talking to and supporting a grieving parent. The innovation met the anticipated learning objectives; learners and faculty, in particular the actor as Mother, expressed the need for a whole day course to allow more time to explore issues and allow breaks due to the highly emotive nature of the day: this will be built in to future course design. Conclusion: This course is innovative and provides useful, and much needed, education to those providing end-of-life care. Reference: 1. Xafis V, Watkins A, Wilkinson D. Death talk: Basic linguistic rules and communication in perinatal and paediatric end-of life discussions. Patient Education and Counselling2016;99:555–561.